A narrative review on the role of carbon nanoparticles in oncology. (17th August 2022) - Watt, Meghan M.; Moitra, Parikshit; Sheffield, Zach; Ostadhossein, Fatemeh; Maxwell, Elizabeth A.; Pan, Dipanjan
Abstract: The lymphatic system is the first site of metastasis for most tumors and is a common reason for the failure of cancer therapy. The lymphatic system's anatomical properties make it difficult to deliver chemotherapy agents at therapeutic concentrations while avoiding systemic toxicity. Carbon nanoparticles offer a promising alternative for identifying and transporting therapeutic molecules. The larger diameter of lymphatic vessels compared to the diameter of blood vessels, allows carbon nanoparticles to selectively enter the lymphatic system once administered subcutaneously. Carbon nanoparticles stain tumor‐draining lymph nodes black following intratumoral injection, making them useful in sentinel lymph node mapping. Drug‐loaded carbon nanoparticles allow higher concentrations of chemotherapeutics to accumulate in regional lymph nodes while decreasing plasma drug accumulation. The use of carbon nanoparticles for chemotherapy delivery has been associated with lower mortality, fewer histopathology changes in vital organs, and lower serum concentrations of hepatocellular enzymes. This review will focus on the ability of carbon nanoparticles to target the lymphatics as well as their current and potential applications in sentinel lymph node mapping and oncology treatment regimens. This article is categorized under: Implantable Materials and Surgical Technologies > Nanoscale Tools and Techniques in Surgery Abstract : Following subcutaneous and intratumoral administration, carbon nanoparticles can selectively enter the lymphatic system and accumulate in regional lymph nodes. For this reason, they are ideal for sentinel lymph node mapping and for use as a delivery vehicle for chemotherapeutics.